The compromise trap : how to thrive at work without selling your soul - Doty, Elizabeth (BK business book., 2009)
Based on in-depth interviews with 55 business people, "The Compromise Trap" describes the balance between doing what it takes to survive at work while keeping one's promises, saying what one really thinks, and still functioning within an organization